ATRIAL FIBRILLATION AND ARTERIAL HYPERTENSION. VARIANCE OF SERUM URIC ACID LEVELS IN BOTH DISEASES. (June 2018) - Kallistratos, M.; Giannitsi, S.; Poulimenos, L.; Miaris, N.; Koukouzeli, A.; Khashlok, L.A.; Kouremenos, N.; Tsinivizov, P.; Kontogiannis, N.; Chamodraka, E.; Athanasiou, D.; Kalogeris, A.; et al.
Abstract : Objective: Atrial fibrillation and arterial hypertension share common risk factors such as obesity, diabetes mellitus, alcohol consumption etc. There is evidence however that the aforementioned risk factors are associated with serum uric acid (SUA) levels. We sought to assess the relation of SUA levels with arterial blood pressure (BP) levels and the incidence of atrial fibrillation Design and method: We prospectively enrolled 568 hypertensive patients (mean age 63 ± 10 years) presented for evaluation in the Hypertension clinic. All patients underwent 24-hour holter monitoring for the detection of atrial fibrillation (AF). Patients with documented AF in 24 hour recordings or patients with a history of AF were defined as AF patients. In all subjects routine blood chemistry, including SUA determination, echocardiographic examination, office and 24 h ambulatory blood pressure (BP) monitoring were obtained. In all patients data regarding lifestyle habits (smoking, alcohol consumption and exercise) were recorded. Results: From 568 hypertensive patients, 77 patients (13%) had atrial fibrillation. Mean average 24 hour systolic blood pressure (SBP) was 132 ± 15 mmHg, mean 24 hours average diastolic blood pressure (DBP) was 77 ± 10 mmHg. Spearman analysis showed that SUA levels were significantly and positively associated with the average 24 hours systolic blood pressure levels (rs = 0.092, p < 0.05 for SBP) but not with diastolic BP levels (rs = 0.06, p > 0.05). Serum uric acid levels in patients with atrial fibrillation were statistically significantly higher than those without (Z = −5, 3, p < 0.001). In addition, SUA levels were highly correlated with all the major risk factors predisponding for the development of arterial hypertension or AF. Specifically SUA levels were significantly higher in males (Mann-Whitney U = 25158.500, p < 0.01), in elder patients (rs = 0.117, p < 0.01), in patients with increased body mass index (rs = 0.337, p < 0.01), with diabetes (Mann-Whitney U = 25445.500, p < 0.05). Conclusions: Increased SUA levels were significantly associated with the incidence of atrial fibrillation and systolic BP levels as well as with the majority of the risk factors predisposing for the development of both diseases.